If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3x + 1) + -2(X + -5) = x + 31 Reorder the terms: 3(1 + 3x) + -2(X + -5) = x + 31 (1 * 3 + 3x * 3) + -2(X + -5) = x + 31 (3 + 9x) + -2(X + -5) = x + 31 Reorder the terms: 3 + 9x + -2(-5 + X) = x + 31 3 + 9x + (-5 * -2 + X * -2) = x + 31 3 + 9x + (10 + -2X) = x + 31 Reorder the terms: 3 + 10 + -2X + 9x = x + 31 Combine like terms: 3 + 10 = 13 13 + -2X + 9x = x + 31 Reorder the terms: 13 + -2X + 9x = 31 + x Solving 13 + -2X + 9x = 31 + x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -2X + -13 + 9x = 31 + -13 + x Reorder the terms: 13 + -13 + -2X + 9x = 31 + -13 + x Combine like terms: 13 + -13 = 0 0 + -2X + 9x = 31 + -13 + x -2X + 9x = 31 + -13 + x Combine like terms: 31 + -13 = 18 -2X + 9x = 18 + x Add '-9x' to each side of the equation. -2X + 9x + -9x = 18 + x + -9x Combine like terms: 9x + -9x = 0 -2X + 0 = 18 + x + -9x -2X = 18 + x + -9x Combine like terms: x + -9x = -8x -2X = 18 + -8x Divide each side by '-2'. X = -9 + 4x Simplifying X = -9 + 4x
| 15(v+2)-3v=4(3v+4)-20 | | 7+-3=39 | | 10y=990 | | 3x=2(4-x) | | y-7.76=2.53 | | -1=-3*1-2 | | (4x+2)=(7x-21) | | 9m+20=-10m-18 | | 15.5=J--7.5 | | 4m-3=-9 | | 3*7-4*4=5 | | -6(-5m+8)-4=-172 | | 10(s-10)=-124 | | 6(x-4)-5x=3(x-8)-2x | | 5x^6+17x^5-x^3+6x+9=0 | | 2x+14-8x=17-13x+7x-3 | | 5=3*1+1 | | x/9-5=-2 | | -26=c-805 | | 11=7-g/3 | | 4(3x+1)=-5(1-2x)+3x | | 3*2+3=3 | | 5(32+6)=3 | | 18/42-7/42 | | w=v-ih | | 1/2n=40 | | 11-4(a+20)=8+a | | -(x-3)+2=5x-8 | | 7h-3k-2k-(-h)= | | u-9.52=1.95 | | 1x+2y=47 | | 3x+ax=7+b |